KURIKULUM BERBASIS CINTA SEBAGAI UPAYA PEMBENTUKAN KARAKTER SISWA DI SDIT KAMILIYAH PALEMBANG-KOTA PALEMBANG - Ali Murtadho, Muhammad; Ahmad Zainuri; Muslim Ghani Yasir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of digital technology has posed significant challenges to students’ character formation, particularly for Islamic educational institutions that emphasize not only cognitive achievement but also moral and spiritual development. This study aims to analyze the concept, implementation, and contribution of a Love-Based Curriculum in shaping students’ character at SDIT Kamiliyah Palembang. The research employs a qualitative descriptive approach with a case study design. The participants consisted of one principal, three teachers, and six students selected purposively. Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was ensured through source and technique triangulation. The findings indicate that the Love-Based Curriculum is conceptualized as an educational approach grounded in compassion (mahabbah), empathy, role modeling, and reflective dialogue. Its implementation is integrated into lesson planning, teacher–student interactions, restorative discipline practices, and school culture, including religious habituation and the 5S practice (smile, greet, and salute). This approach fosters intrinsic motivation, moral awareness, and the development of a sustainable religious habitus among students. Moreover, it creates a psychologically safe learning environment that encourages openness, reflection, and self-improvement. The study concludes that love functions as a systemic pedagogical paradigm integrating psychological, moral, and spiritual dimensions within Islamic education. The Love-Based Curriculum offers a holistic and contextual character education model in responding to the character crisis in the digital era.